(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Globalization and information technology (IT) have altered how businesses conduct their operations. The IT system is deployed and integrated in virtually all businesses who have made significant investments in IT infrastructure for the long-term development of their business. The use of e-commerce (EC) as a means of conducting commercial transactions is causing growing concern. The global economy is undergoing a transformation. Through the use of internet technology, all businesses are converted into information based operations. The rate of technological change is now so rapid that contemporary internet commerce is causing major economic changes that are affecting every sector. The Internet has broadened the scope of businesses. The enormous amount of business information made available by the worldwide network that enables the collection of information between companies, corporations, their customers, and different business divisions is growing at an exponential rate. Virtual value chains built on information are critical to every company’s operational and strategic success. The significance, facilitators, advantages, difficulties, and extent of electronic commerce in the Indian market were addressed in this review study.